LEGAL ASPECTS OF CRIMINAL ILLEGAL MANUFACTURE, PROCESSING, PURCHASE, STORAGE, TRANSPORT, TRANSFER OR SALE OF NARCOTIC DRUGS OR PSYCHOTROPIC SUBSTANCES - Kulbayev Ерлан Мухитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
In a scientific article, the author thoroughly considering the legalization of money or other property acquired by illegal means.